How Indonesian Bloggers Empower Civil Society - Ana Nadya Abrar (The Indonesian Journal of Communication Studies, 2009)
This paper presents a research report on the characteristics of information presented in eight blogs in 2008 and how those eight bloggers (blog owners) empowered civil society through their published articles. Field data demonstrate that the articles they published contained empowerment messages, achieved positive responses from the blog visitors, and implied that the blog owner conducted their social function as bloggers. However, the dispersed information in the blogs has only obtained one response from each visitor. That information could not develop a dialog for creating a consensus on what civil society should do when they encounter the state. Having seen the relations between persons and blog, bloggers were reluctant to apply interactivity principle when they receive responses from their blog visitors. They were receptive, appreciative, and sympathetic to individuals in responding to their articles. However, only a few of them wished that their participants changed and developed. They expected their changed and grown turned into empowered citizen when they faced the state. In short, Indonesian bloggers are only partially in empowering civil society.